Слеза Евы: [роман] / Елена Дорош - Дорош Елена (Вечерний детектив, 2023)
Экземпляры: ЦБ (20230511) / Инвентарный номер: 58796 / Цена: 312.09 / Сис.шифр: 84(2=411.2)6 / Авт.знак: Д 69 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-44